Venous sinus thrombosis during COVID-19 infection in pregnancy: a case report - Gunduz, Zahide Betül (São Paulo Medical Journal, 2021)
BACKGROUND: Although it is known that the new coronavirus disease (COVID-19), which was first seen in Wuhan, China, in December 2019 and has affected the whole world, mainly targets the respiratory tract, cases of this disease with a wide clinical spectrum are emerging as information is shared. CASE REPORT: We present the case of a pregnant woman who was diagnosed with venous sinus thrombosis after she developed headache and hemiparesis. Polymerase chain reaction (PCR) positivity lasted for two weeks after COVID-19 had been diagnosed. CONCLUSIONS: In patients with suspected COVID-19, especially in the presence of causes of hypercoagulability and presence of atypical features, venous sinus thrombosis needs to be kept in mind in making the differential diagnosis.